Greenery : ecocritical readings of late medieval English literature - Rudd, Jill (Manchester medieval literature and culture., 2007)
Humankind has always been fascinated by the world in which it finds itself, and puzzled by its relations to it. Today that fascination is often expressed in what is now called?green? terms, reflecting concerns about the non-human natural world, puzzlement about how we relate to it, and anxiety about what we, as humans, are doing to it. So called green or eco-criticism acknowledges this concern. Greenery reaches back and offers new readings of English texts, both known and unfamiliar, informed by eco-criticism. After considering general issues pertaining to green criticism, Greenery moves on to.